Establishing Recency and Updating Needs for Cochrane Reviews on Selected Complementary Medicine Interventions: Study Protocol - Pratt, Misty; Hutton, Brian; Wieland, Susan; Ahmadzai, Nadera; Skidmore, Becky; Moher, David (Université d'Ottawa | University of Ottawa, 2017)
Previous research evaluating a cohort of published systematic reviews demonstrated that 7% of reviews were out of date by the time of publication while as many as 23% went out of date within two years of being completed. The utility of systematic review-based evidence depends on their remaining up-to-date. As such, the Cochrane Complementary Medicine Field and the Knowledge Synthesis group at the Ottawa Hospital Research Institute (OHRI) have determined a set of existing reviews of interest for which signal detection work using the Ottawa Method’s qualitative/quantitative signal detection approach and some additional considerations will be performed.
Keywords: signal detection; systematic review